Coupled changes in hippocampal structure and cognitive ability in later life. Issue 2 (4th January 2018) - Anblagan, Devasuda; Valdés Hernández, Maria C.; Ritchie, Stuart J.; Aribisala, Benjamin S.; Royle, Natalie A.; Hamilton, Iona F.; Cox, Simon R.; Gow, Alan J.; Pattie, Alison; Corley, Janie; Starr, John M.; Muñoz Maniega, Susana; et al.
Abstract: Introduction: The hippocampus plays an important role in cognitive abilities which often decline with advancing age. Methods: In a longitudinal study of community‐dwelling adults, we investigated whether there were coupled changes in hippocampal structure and verbal memory, working memory, and processing speed between the ages of 73 ( N  = 655) and 76 years ( N  = 469). Hippocampal structure was indexed by hippocampal volume, hippocampal volume as a percentage of intracranial volume (H_ICV), fractional anisotropy (FA), mean diffusivity (MD), and longitudinal relaxation time (T1). Results: Mean levels of hippocampal volume, H_ICV, FA, T1, and all three cognitive abilities domains decreased, whereas MD increased, from age 73 to 76. At baseline, higher hippocampal volume was associated with better working memory and verbal memory, but none of these correlations survived correction for multiple comparisons. Higher FA, lower MD, and lower T1 at baseline were associated with better cognitive abilities in all three domains; only the correlation between baseline hippocampal MD and T1, and change in the three cognitive domains, survived correction for multiple comparisons. Individuals with higher hippocampal MD at age 73 experienced a greater decline in all three cognitive abilities between ages 73 and 76. However, no significant associations with changes in cognitive abilities were found with hippocampal volume, FA, and T1 measures at baseline. Similarly, no significant associations were found between cognitive abilities at age 73 and changes in the hippocampal MRI biomarkers between ages 73 and 76. Conclusion: Our results provide evidence to better understand how the hippocampus ages in healthy adults in relation to the cognitive domains in which it is involved, suggesting that better hippocampal MD at age 73 predicts less relative decline in three important cognitive domains across the next 3 years. It can potentially assist in diagnosing early stages of aging‐related neuropathologies, because in some cases, accelerated decline could predict pathologies. Abstract : Longitudinal change in each hippocampal variable. Each participant has a single point at the initial scanning wave (mean age: 73; red) and at the follow‐up wave (mean age: 76; purple). Participants who contributed data at both waves have their points connected by a gray line. Volume = hippocampal volume (mm 3 ); Percentage Volume = hippocampal volume as a percentage of ICV; FA = hippocampal fractional anisotropy; MD = hippocampal mean diffusivity (mm 2 s −1 ); T1 =  hippocampal T1 (s).